Big-Eyed, Geocoris spp. (Insecta: Hemiptera: Lydaeidae) - Frank W. Mead (EDIS, 2004)
Big-eyed bugs are small insects (approximately 1/6 inch long) that occur in many parts of the world. They are generally regarded as beneficial because they prey upon numerous kinds of insect and mite pests of turf, ornamental and agricultural crops. Big-eyed bugs are among those insects receiving research attention in Florida (and elsewhere) for their value as predators. To aid in identification of big-eyed bugs in Florida, a key to adults and late instar nymphs is provided in this publication. This document is EENY-252 (originally published as DPI Entomology Circular 121), one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: November 2001. Revised: October 2004.